PENGARUH PENDEKATAN MATEMATIKA REALISTIK TERHADAP KEMAMPUAN BERPIKIR KREATIF PESERTA DIDIK KELAS V DI SDN KAPUK 14 PAGI JAKARTA BARAT - Christine, Mutiara; Yuhana, Yuyu; Yandari, Indhira Asih Vivi (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2024)
This study aims to determine the effect of the realistic Mathematics approach on the creative thinking skills of fifth grade students at SDN Kapuk 14 Pagi, West Jakarta. The method used is an experiment with Quasi Experimental Pretest Posttest Only Control Group Design, with the subjects of the study were fifth grade students of SDN Kapuk 14 Pagi, Class VA as the control and VB as the experimental class with a total of 59 students. Data collection techniques use tests and documentation. Data analysis techniques use the Independent T-test. Before conducting the study, a pretest was conducted on the experimental class with an average value of 34.07 and the control class with an average value of 31.16. Based on the results of the study, the average posttest value obtained from the creative thinking skills using the realistic Mathematics approach was 81.21 and for learning that did not use the realistic Mathematics approach was 50.00. From the hypothesis testing, the t-table value was obtained 1.672 < t-count 9.50 which indicates that H0 is rejected, namely there is a high difference in creative thinking ability between students who receive realistic Mathematics approach treatment and students who receive expository approach treatment. Thus, the realistic Mathematics approach has an effect on the creative thinking ability of class V students of SDN Kapuk 14 Pagi.